Bezold–Jarisch reflex mediated syncope in pulmonary arterial hypertension: An illustrative case series. (30th October 2022) - Agboola, Kolade M.; Kowlgi, Gurukripa N.; Csecs, Ibolya; DuBrock, Hilary M.; Cajigas, Hector R.; Allison, Thomas G.
Abstract: We present a novel description of Bezold–Jarisch Reflex (BJR) during cardiopulmonary exercise testing (CPET) in three young female patients with Group 1 pulmonary arterial hypertension (PAH). These three cases presented within 26 months, representing only 0.8% of 11, 387 tests on patients with PAH undergoing CPET during this time frame.